O uso da sintaxe espacial na análise do desempenho do transporte urbano: Limites e potencialidades - Rafael Henrque Moraes Pereira; Ana Paula Borba Gonçalves Barros; Frederico Rosa Borges de Holanda; Valério Augusto Soares de Medeiros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper explores the potentials of applying Space Syntax methodology to analyze the effects of urban configuration on cities' transport performance. The empirical analysis takes as a case study the Federal District (Brazil) and its 19 administrative regions considering its urban road systems configurations. Based on Simple Linear Regressions, the paper analyzes the effects that urban configurations with different integration degrees tend to have on the average time spent in car trips within those road systems. The integration degrees are calculated using traditional configurational variables as well as topo-geometric variables. The results indicate that traditional topological measures are of little use in studies on the effects of road configuration on urban transportation performance. In addition, topo-geometric measures have shown much better results. Finally, preliminary findings suggest that more integrated and compact road systems (regarding topological and geometrical terms) tend to provide more efficient urban configurations for the cities' transport performance.
Keywords: C65; C88; R4; R49; 330